Smart UX Method Selection with UXNator - Oliveira, Solano; Gadelha, Bruno; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
UX assessment plays a key role in the development of user-quality software systems. However, the large number of available methods makes it challenging to choose the most suitable one for UX evaluation. In this paper, we present UXNator, a tool that advances the field by recommending UX methods through a filtering process that gathers input from stakeholders. We conducted a feasibility study, collecting feedback on UXNator’s performance. Both positive and negative perceptions were considered to identify improvement areas. We plan to enhance UXNator based on this feedback, aiming for it to become a standard tool for UX method recommendations.